2016
DOI: 10.3390/molecules21111427
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Manganese(III) Ferrocenyl-β-Diketonato Complexes Revealed by Charge Transfer and Multiplet Splitting in the Mn 2p and Fe 2p X-Ray Photoelectron Envelopes

Abstract: Abstract:A series of ferrocenyl-functionalized β-diketonato manganese(III) complexes, [Mn(FcCOCHCOR) 3 ] with R = CF 3 , CH 3 , Ph (phenyl) and Fc (ferrocenyl) was subjected to a systematic XPS study of the Mn 2p 3/2 and Fe 2p 3/2 core-level photoelectron lines and their satellite structures. A charge-transfer process from the β-diketonato ligand to the Mn(III) metal center is responsible for the prominent shake-up satellite peaks of the Mn 2p photoelectron lines and the shake-down satellite peaks of the Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…16,17,28,[34][35][36][37] On account of the V-shaped curve found between the Gordy group electronegativity, c R , and the Hammett constants of different R-groups, 6 the V-shaped curve found between the Hammett constants and the binding energies of the Fe 2p and Fe 3p photoelectron lines was not unexpected. V-shape correlations obtained with Hammett constants are not uncommon, there are many reports of V-or U-shaped curves linking Hammett constant with other physical parameters, including kinetic constants and degree of substitution.…”
Section: Research Articlementioning
confidence: 87%
“…16,17,28,[34][35][36][37] On account of the V-shaped curve found between the Gordy group electronegativity, c R , and the Hammett constants of different R-groups, 6 the V-shaped curve found between the Hammett constants and the binding energies of the Fe 2p and Fe 3p photoelectron lines was not unexpected. V-shape correlations obtained with Hammett constants are not uncommon, there are many reports of V-or U-shaped curves linking Hammett constant with other physical parameters, including kinetic constants and degree of substitution.…”
Section: Research Articlementioning
confidence: 87%
“…Comparable shake-down satellites were reported in a previous study, for the photoelectron lines associated with the Fe 2p electrons of the Fecontaining ligand, for related [Mn III (ferrocenyl-b-diketonato) 3 ] complexes. 23 In addition, the latter charge transfer model also accounts quantitatively for the observed intensities of the Fig. 4 Relationship between Sc R , the sum of the Gordy scale group electronegativities of the R-groups on the b-diketonato ligand of complexes 1-14, with (A) the maximum binding energy (BE Mn 2p 3/2main ) of the main Mn 2p 3/2 photoelectron line, as well as with (B) the spin orbit splitting of the maximum binding energy (DBE 1 ) of the main Mn 2p 3/2 and Mn 2p 1/2 photoelectron lines (DBE 1 ¼ BE Mn 2p 1/2main À BE Mn 2p 3/2main ).…”
Section: Nomentioning
confidence: 99%
“…[17][18][19][20][21] Due to the four unpaired d electrons of high spin Mn(III) complexes, their geometry displays the Jahn-Teller effect and also the X-ray photoelectron spectroscopy (XPS) lines of these complexes split into many peaks, due to a coupling interaction between the unpaired core p-electrons (originating aer photoemission) and the unpaired valence d-electrons. 22 Recently an X-ray photoelectron spectroscopy study on [Mn III (ferrocenyl-bdiketonato) 3 ] complexes, where the b-diketonato ligand contained at least one ferrocenyl group, 23 showed that a charge-transfer process from the b-diketonato ligand to the Mn(III) metal centre is responsible for prominent shake-up satellite peaks of the main Mn 2p photoelectron lines. These results further showed that the binding energies of the Mn 2p photoelectron lines are linearly inuenced by the sum of the Gordy scale group electronegativities 24 of the different R groups attached to the b-diketonato ligands (RCOCHCOFc) À (Fc ¼ ferrocenyl group), varying over a binding energy range of 0.55 eV.…”
Section: Introductionmentioning
confidence: 99%
“…These satellite peaks are due to final state effects and appear either when the photoelectron imparts energy to another electron of the atom, thereby loosing kinetic energy and appearing at a higher energy in the spectrum [50,57,58], or when a ligand-to-metal or metal-toligand charge transfer occurs during photo-ionization [59]. In the case of ligand-to-metal charge transfer for example, metal shake-up peaks are accompanied by comparable shake-off satellites for the photoelectron lines of the ligand elements, although not commonly observed [60].…”
Section: Xps Satellite Peaks (Final State Effect)mentioning
confidence: 99%
“…In transition metal complexes, satellite peaks located at binding energies that are a few eV lower than the main photoelectron line, are associated with charge transfer from the element under investigation (in this case Sb) to the rest of the compound (in this case Mo), and are produced by a shake-off mechanism [50]. The intensity of the satellite peak is indicative of the amount of charge transfer taking place during photoionization [60]. The larger the peak, indicated…”
Section: Xps Satellite Peaks (Final State Effect)mentioning
confidence: 99%